Abnormal thermal conduction in argyrodite-type Ag9FeS6-xTex materials. (July 2021) - Jin, Z.; Xiong, Y.; Zhao, K.; Dong, H.; Ren, Q.; Huang, H.; Qiu, X.; Xiao, J.; Qiu, P.; Chen, L.; Shi, X.
Abstract: Rationalizing the underlying mechanism that correlates phonon transport with structural complexity is crucial for the development of materials with ultralow thermal conductivity. Herein, we investigated the abnormal thermal transport and lattice dynamics in Ag9 FeS6 -x Te x argyrodite-type compounds via a combination of properties characterization, model analysis, and theoretical calculations. Our results show that the ordered α-phase and disordered β-phase of Ag9 FeS6 -x Te x exhibit distinct temperature dependency of lattice thermal conductivity κ L . Specifically, the κ L of ordered α-phase shows a crystalline characteristic with a pronounced Umklapp peak observed at ∼10 K, while the κ L of disordered β-phase monotonously increases in the whole temperature range without a peak or plateau. Such different thermal transport behavior is a result of different contributions to the reduction of κ L from the structural disorder and the low-lying multi-Einstein oscillators, both of which are associated with the weakly bonded Ag + ions. The knowledge depicted here provides fundamental insights into the extraordinary thermal transports in materials with structural disorder and/or weak chemical bonds. Graphical abstract: We demonstrated the distinct thermal transport behavior for the ordered α-phase and disordered β-phase of Ag9 FeS6 -x Te x was attributed to their difference in structural disorder, chemical bonding, and lattice dynamics. Image 1 Highlights: Synthesizing argyrodite-type Ag9 FeS6- x Te x with wide compositional range despite large atomic size mismatch between S and Te. Obtaining ordered α-phase and/or disordered β-phase through tuning the Te content. Revealing the origin of distinct thermal conduction in the ordered α-phase and disordered β-phase.